PENGARUH BRAND IMAGE, KUALITAS PRODUK, HARGA DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEMEN DI PT SEMEN INDONESIA LOGISTIK CABANG GULOMANTUNG GRESIK - Fitriani, Annisatun Nur (Universitas Muhammadiyah Gresik, 2019)
This study aims to analyze the influence of Brand Image variables, Product Quality, Price and Service Quality on Purchasing Decisions at PT. Semen Indonesia Logistics Branch of Gulomantung Gresik. This type of research uses quantitative with a sample of 154 consumers. The sampling technique used Incidetal Sampling. The results of the study proved to show that the Brand Image variable, Product Quality, Price had a positive and significant effect and the service quality variable had a negative and significant effect on the Purchase Decision.